Research Progress of Exosomes in Bone Diseases: Mechanism, Diagnosis and Therapy - Meng, Fanying; Xue, Xu; Yin, Zhifeng; Gao, Fei; Wang, Xiuhui; Geng, Zhen (Frontiers in Bioengineering and Biotechnology, 2022)
Graphical Abstract